2022
DOI: 10.1039/d1tc05773a
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functional switch effect in interlocking molecular rotators-on-graphene systems using electric fields

Abstract: One approach to design electronic devices is to use molecules whose configuration can be actively modified to control their electrical conductivity. A recent theoretical study provides a candidate in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 71 publications
(136 reference statements)
0
10
0
Order By: Relevance
“…The exchange correlation functional was also selected as GGA-PBE. A double-ζ plus polarization basis adopted to the electron wave function [9,10,[47][48][49]. In geometric optimization, the convergence criterion of the Hamiltonian was set at 10 −5 eV.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The exchange correlation functional was also selected as GGA-PBE. A double-ζ plus polarization basis adopted to the electron wave function [9,10,[47][48][49]. In geometric optimization, the convergence criterion of the Hamiltonian was set at 10 −5 eV.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In order to balance the efficiency and accuracy of the calculations, the cutoff energy was set to be 150 Ry, and the force tolerance was set to be 0.02 eV Å −1 . 43–46 Using the Landauer formula, the current under the bias voltage V b was defined as:…”
Section: Computational Detailsmentioning
confidence: 99%
“…TMDCs-based vdW is an emerging study tendency for its applications in electronic appliances. [3,4] Recently, Siao et al [5] presented use of WSe 2 /WS 2 vdW heterostructures band offset engineering for nonvolatile memory application. The device maintains a high extinction ratio of 10 6 at 34 V. Previous studies have suggested that MXene creates deep applications in photoelectricity, electron carrier, nanoscale superconductivity, and light sensing.…”
Section: Introductionmentioning
confidence: 99%